Maedi-visna infection in Pomeranian Coarsewool Sheep in Germany: seroprevalence, environmental and genetic risk factors - Frölich, Cassandra; Beato, Maria Serena; Gobbi, Paola; Mrabet, Sara; Lühken, Gesine; Ganter, Martin (Frontiers in Veterinary Science, 2025)
Small ruminant lentiviruses (SRLV) cause maedi-visna (MV), an incurable, wasting disease, affecting sheep worldwide. This study evaluated the seroprevalence of maedi-visna virus (MVV) in the native German sheep breed Pomeranian Coarsewool Sheep (RPL) and environmental and genetic risk factors for individual and flock-level seropositivity. A total of 849 samples from 35 farms across nine German states were analyzed for MVV antibodies with an enzyme-linked immunosorbent assay (ELISA). Individual seroprevalence and clinical prevalence were 3.5% (30/849) and 13.3% (4/30), respectively. Seropositive sheep were detected in six flocks, with prevalences between 5.3 and 37.5%. Flocks in Eastern Germany and sheep older than 3 years showed the highest seroprevalence. Purchase of ewes was the main environmental risk factor for seropositivity. ELISA-based serotyping of SRLV in the MVV-positive sheep identified, besides genotype A, for the first time in Germany genotype B, whereas molecular genotyping, based on Sanger sequencing, identified only genotype A (A1, A3, A21, and A21-like). Apart from the obvious inconsistencies between the results of these two methods, presence of different viral sero- or genotypes suggest multiple virus introduction routes. Sequencing of exons 2 and 3 of the transmembrane protein 154 gene (TMEM154) of 530 sheep revealed non-synonymous variation at codons 35, 44 (known to be in linkage with a frame-shift variant coded in exon 1), and 70. Analysis of association between the putatively protective TMEM154 codon 35 genotype KK and MVV seropositivity showed only a tendency toward significance (p = 0.088), whereas seroprevalence was significantly (p = 0.001) lower in sheep exclusively carrying the K allele at codon 35 and/or the M allele at codon 44. In contrast, MVV seropositivity was significantly higher in sheep with one or two I alleles at codon 70 (p = 0.045). Despite a low seroprevalence in the RPL breed in Germany, regular MVV monitoring is strongly recommended to avoid its spread. An eradication program based on serological testing and removal of seropositive sheep should be implemented. Selection for certain TMEM154 alleles in affected flocks could support eradication measures, but their effect on MVV susceptibility in this breed requires further investigation.